PENGEMBANGAN MODUL PAI KELAS III DI SD N 03 LUBUAK BATINGKOK KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Mufidah Hayati; Wedra Aprison (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is in the field of education, the most basic development of which is the development of modules as a source of learning. Module development is carried out to help smooth the teaching and learning process. The development of this module is carried out because in reality the existing modules are still far from the desired expectations and the module is not in the proper format or the components in the module are not yet complete. Researchers are interested in conducting research in the form of developing modules so that the module can fit the format, have complete components and can produce a valid module. The type of research used in this study is Research and Development (R&D), namely the type of research used to produce a particular product in this case is a module and to test the validity of the developed module. In collecting research data, researchers used data collection techniques through two sources, namely primary data sources from interviews, assessment sheets, and documentation, also from secondary data sources, researchers conducted reference studies from books and journals on the internet. Analysis of the data used in this study used descriptive qualitative analysis, namely by describing the results of product development for class III PAI modules. Based on the results of the research that the researcher did, the researcher has succeeded in developing a product in the form of a valid class III PAI module, an PAI module that is in accordance with the proper format, and is complete. The results of the module validation that have been carried out have gone through the stages of validation by material experts and assessment by educational practitioners, so it can be seen that the module eligibility standards according to material experts are based on 25 statements that become criteria from the assessment aspect, 90% results are obtained with very high criteria, while the assessment from education practitioners based on 10 statements that became aspects of the assessment obtained 97% results with very high criteria and it can be concluded that the module that has been developed is feasible to use. Keyword: Module Development, PAI, Elementary School (SD)